Living in Transition in the Atlantic World: Democratic Revolution and Commercial Society in the Political Writings of Thomas Paine - Matteo Battistini (Centre de Recherches sur les Mondes Américains, 2012)
By reconstructing Thomas Paine's vision of the Atlantic world, this paper will discuss three main points. Firstly, it will be demonstrated that Paine’s political thought articulated an understanding of the historical and theoretical relationship between commercial society and representative democracy. Thiswill highlight the convergences and divergences between the American and French revolutions, and the mechanisms of political and social transition that moved the Atlantic world into the nineteenth century. Secondly, it will be argued that this historical and theoretical relationship between commercial society and representative democracy, found in Paine’s work, claims to reconsider contrasting conceptions of Atlantic history. From its beginnings, Atlantic history has been treated as political history, but new Atlantic studies - such as social and economic histories or histories of material culture - have done much to eclipse the political aspects of the history of the Atlantic world by looking at other, equally interesting factors. By reading Paine, this paper will instead argue that a faithful account of Atlantic history cannot hold on to a strict distinction between the political and social. Instead, the political and the societal are interrelated, both conceptual camera lenses through which the Atlantic world during this era can be more accurately captured.